Research on Determination of Bearing Capacity of Existing Reinforced Concrete Beam Considering Probability Distribution Characteristics - Kang, Il Chan; Ri, Chol Myong (International Journal of Architecture and Urbanism, 2024)
This paper determined the bearing capacity of existing reinforced concrete beams by considering the probability distribution characteristics of technical assessment data for existing buildings, which are objectively existing, unlike designed structures.